Presence of Tim3+ and PD‐1+ CD8+ T cells identifies microsatellite stable colorectal carcinomas with immune exhaustion and distinct clinicopathological features. Issue 2 (9th April 2022) - Klapholz, Max; Drage, Michael G; Srivastava, Amitabh; Anderson, Ana C
Abstract: Colorectal carcinoma (CRC) is the second leading cause of cancer mortality worldwide. CRC is stratified into two major groups: microsatellite stable (MSS) and microsatellite instability‐high (MSI‐H). MSS CRC constitutes the majority of cases, has worse overall prognosis, and thus far has failed to respond to immunotherapies targeting the immune checkpoint receptors PD‐1, PD‐L1, and CTLA‐4. Here we examined the alternate immunotherapy targets Tim‐3 and Lag‐3, as well as PD‐1, on immune cells in a cohort of MSS CRC using immunohistochemistry and flow cytometry together with mutational analysis and clinical data. We found that PD‐1 was variably expressed across CD4 + tumor‐infiltrating lymphocyte (TIL) subtypes, and Tim‐3 was mostly restricted to CD4 + regulatory T cells. Lag‐3, when detected by flow cytometry, was largely coexpressed with Tim‐3 and PD‐1 in CD4 + TILs. Furthermore, Tim‐3 + PD‐1 + CD8 + TILs accumulated in the tumor and exhibited a dysfunctional or 'exhausted' phenotype. Notably, we observed a subset of patients with a high proportion of Tim‐3 − PD‐1 − CD8 + TILs and, conversely, a low proportion of Tim‐3 + PD‐1 + CD8 + TILs, thus stratifying MSS CRC patients based on a feature of immune exhaustion (MSS‐ImmEx). MSS‐ImmEx hi patients had abundant Tim‐3 + PD‐1 + CD8 + TILs, PD‐1 + CD4 + effector, and regulatory T cells, and were enriched for left‐sided colon tumors and mutations in the APC tumor‐suppressor gene. We further investigated the spatial organization of Tim‐3, Lag‐3, PD‐1, and PD‐L1 by immunohistochemistry and found higher levels in the tumor margin; however, MSS‐ImmEx hi tumors exhibited a higher density of Tim‐3 + cells in the tumor center over MSS‐ImmEx low tumors. Immunofluorescence revealed a higher density of PD‐1 + /CD8 + cells in the tumor center in this group. Our findings identify a subset of MSS CRC that exhibits evidence of higher prior immune activation (MSS‐ImmEx hi ) in which therapies targeting Tim‐3 in conjunction with anti‐PD‐1 or other immunotherapies may provide clinical benefit. © 2022 The Pathological Society of Great Britain and Ireland.